Supportive Infusions in Integrative Breast and Gynecological Oncology - Report on Patients' Satisfaction and Self-reported Effects and Side Effects - Hack, Carolin; Antoniadis, Sophia; Beckmann, Matthias; Brandl, Anna; Fasching, Peter; Hackl, Janina; Langemann, Hanna; Stock, Katja; Weber, Natalie; Theuser, Anna-Katharin (Geburtshilfe und Frauenheilkunde, 2018)
Background During cancer therapy, many patients suffer from malnutrition or vitamin deficiency. Treatment for nutrition-related deficiencies should therefore include nutritional therapy and possibly oral or intravenous substitution of micronutrients. Little information exists on multinutrient infusion therapies. The aim of this study was to develop standardized infusion protocols for integrative medicine infusions with micronutrients (IMed infusions) and to report on side effects of the treatment and patients' satisfaction with it. Methods For the IMed consultancy service, four special formulas for intravenous use were developed in cooperation with the pharmacy at Erlangen University Hospital. A retrospective cross-sectional study was conducted between October 2015 and January 2018 in which 45 patients with gynecological or breast cancer (BC) and IMed infusion therapy were included. Follow-up data were obtained from 20 patients using a standardized questionnaire on IMed infusions. Results A total of 280 IMed infusions were administered in the study period. The majority of the patients received an IMed regeneration infusion (78%). The majority of the patients had BC and were receiving chemotherapy. Most patients reported a high or very high level of satisfaction with the organization (60%), general treatment (65%) and counseling (85%). Subjective improvement in their disease-related and therapy-induced symptoms, such as fatigue, polyneuropathy and physical efficiency, was reported by 70% of the patients, while 75% reported a subjective increase in quality of life. Side effects were rare and minor. Conclusions Therapy with IMed infusions in women with BC or gynecological cancer requires the same standards set for drug therapy. Although vitamins represent dietary supplements, appropriate assessment of the patient's medical history is needed and patients must receive appropriate information. For this purpose, standardized processes, as in the context of an IMed consultancy service, are helpful.
EVALuna2:209954